Workplace Social Support in Coronatime as a Moderator Between Leader–Subordinate Fit and Entrepreneurial Behaviour - Jinan Shihab Ahmed (Universitas Muria Kudus, 2022)
this study investigated the moderating effect of workplace social support on the relationship between leader–subordinate fit and entrepreneurial behaviour in an Iraqi private higher education institution. A sample of 127 respondents was selected and a questionnaire was administered to them via Google Form. The data thus collected were analysed using JASP. Consistent with the P-E fit theory, the results revealed that supplementary fit (β = 0.44, t = 6.65, p .001, 95%CI = 0.29 to 0.53) and complementary fit (β = 0.46, t = 6.91, p .001, 95%CI = 0.31 to 0.56) significantly predicted entrepreneurial behaviours. However, in contradiction to the buffering hypothesis, the semi-partial Bayes Factor (BF) statistics indicate that workplace social support did not play any moderating role in the model. The study concludes with a brief discussion on the results, limitations of the study, and suggestions for further research.